When Less Regulation Means More Complexity: The EU AI Liability Directive Withdrawal and Its Impact on European Technological Competitiveness - Nannini, Luca (Proceedings of the AAAI/ACM Conference on AI, Ethics, and Society, 2025)
This paper examines the February 2025 withdrawal of the European Commission’s AI Liability Directive (AILD) and its implications for European technological competitiveness. It challenges the assumption that deregulation inherently fosters innovation, demonstrating that eliminating harmonized liability rules paradoxically increases regulatory complexity through fragmentation across 27 national regimes. This fragmentation disproportionately burdens European AI companies—particularly startups and SMEs—attempting to scale across the Single Market, while advantaging large non-EU tech companies with greater resources to navigate regulatory complexity. Drawing on empirical evidence across sectors, it presents how well-designed liability frameworks can actually catalyze innovation by establishing market certainty, building consumer trust, and creating positive incentives for safety. Solutions are discussed for integrating liability considerations into Europe’s broader digital sovereignty strategy through targeted harmonization of specific liability aspects and innovation-enabling frameworks, including regulatory sandboxes and compliance-by-design toolkits. This approach positions liability rules as enablers rather than impediments to sustainable technological advancement in the global AI landscape.